The Intelligent System in IT Governance: A review pointing the Institute of Higher Learning in Malaysia - Mukhlas, Amalia; Beh, Delina M.Y.; Ahmad, Aishah (International Journal of Engineering and Technology, 2018)
The established governance of IT in higher learning institution is necessary for institution to address the key issues successfully. This study initiates to investigate existing research of Information Technology Governance (ITG) focusing Institute of Higher Learning (IHL) in Malaysia. The research aims to discover the up-to-date tabulation of Intelligent System (IS) research covered by ITG domain, to identify the structure of research being performed in this area, to identify the outcome produced by conducted study as well as recommendation of study to be performed in future. The investigation performed through a systematic review from literature to answer the research questions. The outcome indicates the opportunity of area to be researched involving intelligent system in ITG domain and intelligent system for decision-making to support ITG in IHL. The qualitative approach found to be the method use for information collection. The approach of multiple case studies and scientific result to support future method is recommended. The contributions of this study are to produce the review and mapping of studies to identify research areas that has been covered besides identifying potential investigation to be explored in future. The significance of our findings is essential for the start-up research of intelligent system in ITG focusing the IHL in Malaysia.